Is extracorporeal shockwave therapy an effective treatment for calcaneal spur? A literature review - Chojniak, Alicja Katarzyna; Kuna, Paweł Jan; Gajda-Bathelt, Monika; Adasiewicz, Julia; Kwaterska, Katarzyna; Benecka, Agnieszka; Janawa, Kamil; Tomaszek, Michał; Michalak, Klaudia; Janowski, Kacper (Quality in Sport, 2025)
Introduction: Calcaneal spurs are common osteophytic outgrowths from the heel bone, found in up to 21% of the population, with prevalence increasing significantly with age. While often asymptomatic, they can cause severe, disabling heel pain, particularly aggravated by weight-bearing. Their development is often linked to chronic traction by soft tissues and associated with plantar fasciitis, though they are also observed in asymptomatic individuals. Risk factors include age, weight, gender, and certain arthritic conditions, underscoring the need to differentiate calcaneal spurs from other causes of heel pain for effective treatment. Aim: The aim of this article is to explore the underlying mechanisms of calcaneal spur and assess the effectiveness of treating it through extracorporeal shockwave therapy. Review methods: A comprehensive analysis of research papers available on PubMed and Google Scholar was conducted using keywords: calcaneal spur, heel spur, bone spur, extracorporeal shockwave therapy, calcaneal spur pathophysiology. Conclusion: Plantar calcaneal spurs, often resulting from chronic mechanical stress and degenerative changes, can significantly impact quality of life. This review indicates that Extracorporeal Shockwave Therapy (ESWT) is a promising non-invasive treatment for symptomatic spurs, effectively reducing pain and inflammation when conservative methods fail. However, further high-quality research is needed to definitively establish its optimal role and protocols.